Quantitative and qualitative analysis of psychosocial factors affecting women’s entrepreneurship - Peris-Delcampo, D.; Núñez, A.; Costa, C. M.; Moriconi, M.; Cantón, E.; Garcia-Mas, A. (Behavioral Sciences, 2023)
This work aims to clarify the psychosocial variables that lead women to undertake and those that prevent them from doing so. Two studies were conducted using a mixed methodology to compensate for the inherent weaknesses of using each approach. The first study was based on the collection of quantitative data using the GloPEW questionnaire with a sample of 296 people. The second study, of a qualitative nature, was carried out through focus groups with a sample of 26 people. The results show that self-efficacy and emotional intelligence are the main factors to develop to promote entrepreneurship among women. Although the data show statistical strength, it seems necessary to expand the sample and incorporate more profiles of female entrepreneurs, for example, with different levels of training, given the complexity and variety of intervening factors.